Globalization and the Muslim world - Hassan, M. Kabir 1963- (Bangladesh Inst. of Islamic Thought, 2003)
Contributed articles.
Contributed articles
Includes bibliographical references
Keywords: Geschichte 1900-2000; Globalisierung; Religion; Wirtschaft; Globalization -- Economic aspects -- Islamic countries; Globalization -- Religious aspects; Islamic countries -- Economic conditions -- 20th century